A METHOD OF CREATING DISTRIBUTED ENGINEERING KNOWLEDGE DATABASES - V. А. Kochurov (Informatika)
The article reviews the principle and methods for creating the models of distributed engineering knowledge as well as software implementation of such models in the form of the Information and Logical Table Server (SILT) resulted in development of a cluster based on the WCF (Windows Communication Foundation) technology and reciprocity of the SILT elements. The cluster might be entered by means of a special web application which is an element of SILT using every device with a web browser and access to the internet.